Decree No. 671 of the year 2014 concerning the export duty imposed on certain kinds of scraps and raw materials / translated by The middle east library for economic services. - Egypt. Ministry of Industry, trade and small & medium projects; The middle east library for economic services, translator. (2025)
Serial No. 75/2014